Profil Perubahan Dimensi Mandibula Selama Fase-Fase Pubertas - Velisya Velisya; Harryanto Wijaya (Fakultas Kedokteran Gigi Universitas Trisakti, 2019)
Background: Growth and development of craniofacial is a must known knowledge for dentists, especially orthodontists. The mandible as part of the craniofacial bone is an important target in orthodontic treatment, especially dentofacial orthopedics during puberty. Optimal results from orthodontic treatment can be achieved through the diagnosis, treatment plan and timing of appropriate treatment interventions, therefore it is important to know the timing of the appropriate intervention to the mandible. The aim of this study is to analyze the profile changes in mandibular dimention during the puberty phase. Materials and Methods: This is an analytical observational study with 120 cephalograph lateral samples of children aged 8-18 years old. Anova test was conducted to analyze differences in mean mandibular growth, as ramus height (Co-Go), corpus length (Go-Gn) and total mandiblar length (Co-Gn) between puberty phases determined by the Cervical Vertebral Maturation System (CVMS) method. Results: There were no Co-Go differences between pre-peak and peak phases (p = 0.314) and peak and post-peak phases (p = 0.164). There were differences in Go-Gn (p = 0,000) and Co-Gn (p = 0.025) between the pre-peak and peak phases. Conclusion: There are differences in mandibular growth profile, especially Go-Gn and Co-Gn between the pre-peak and peak stages of puberty.